2020
DOI: 10.1128/jmbe.v21i1.1881
|View full text |Cite
|
Sign up to set email alerts
|

A Modified CREATE Intervention Improves Student Cognitive and Affective Outcomes in an Upper-Division Genetics Course

Abstract: Many national reports have called for undergraduate biology education to incorporate research and analytical thinking into the curriculum. In response, interventions have been developed and tested. CREATE ( C onsider, R ead, E lucidate the hypotheses, A nalyze and interpret the data, and T hink of the next E xperiment) is an instructional strategy designed to engage st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Variation theory describes the discrepancy between what an instructor intends to accomplish in a curriculum and what individual students may take away from the same in-class activities. , In some instances, students in a course with interactive elements underpredict their academic performance in relation to their actual grade outcomes . Students perceptions of the GCA+ course should be interpreted within this literature framework and existing evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation theory describes the discrepancy between what an instructor intends to accomplish in a curriculum and what individual students may take away from the same in-class activities. , In some instances, students in a course with interactive elements underpredict their academic performance in relation to their actual grade outcomes . Students perceptions of the GCA+ course should be interpreted within this literature framework and existing evidence.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 In some instances, students in a course with interactive elements underpredict their academic performance in relation to their actual grade outcomes. 45 Students perceptions of the GCA+ course should be interpreted within this literature framework and existing evidence.…”
Section: Student Perceptionsmentioning
confidence: 99%
“…In addition to increased science literacy, studies have shown increases in student effective and cognitive gains, increases in student interest in the course material, and increases in students’ confidence in science communication ( 2 4 ). Moreover, educational interventions using PSL at the undergraduate level are well documented and include journal clubs ( 5 , 6 ), variations of consider, read, elucidate the hypotheses, analyze and interpret the data, and think of the next experiment (C.R.E.A.T.E.)…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, educational interventions using PSL at the undergraduate level are well documented and include journal clubs ( 5 , 6 ), variations of consider, read, elucidate the hypotheses, analyze and interpret the data, and think of the next experiment (C.R.E.A.T.E.) ( 2 , 7 12 ), circular response ( 13 ), process-oriented guided inquiry learning (POGIL) activities ( 14 ), Jigsaw activities ( 15 ), Figure Facts ( 16 ), annotated articles ( 17 ), and comprehension exercises ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Often, students highlight long passages or read over unfamiliar jargon without fully comprehending the significance and details of a study. Several approaches have been described to promote the critical reading and analysis of primary literature (4)(5)(6)(7)(8)(9). While these methods provide structure, students often read and analyze in isolation, as the methods do not facilitate virtual and open peer collaboration.…”
Section: Introductionmentioning
confidence: 99%